DIMENSI HUKUM TANGGUNG JAWAB NEGARA TERHADAP LINGKUNGAN DAN ALAM - Faturohman Faturohman; Asnawi Asnawi (Res Justitia : Jurnal Ilmu Hukum, 2022)
In the environmental management system, it is known that the State has power over natural resources. This principle means that the State through the government is authorized to regulate, control and develop all matters relating to environmental management. Article 8 paragraphs (1) and (2) of the Environmental Management Act. The purpose of the research is the protection and management of the environment to determine the State's responsibility in law enforcement against violations of the environment and nature. This research is a normative juridical research with a statutory approach and a case approach. This research uses secondary data, which consists of secondary legal materials and tertiary legal materials. From the results of the study, it was concluded that the certainty of law enforcement is the government's responsibility for environmental and natural violations